The Lance and the Arc, or for a quilombist-becoming of art - Vasconcellos, Jorge (Farol, 2021)
We affirm that there is an ongoing minority tour of contemporary art, from which we argue that it is possible to think that, in certain artistic practices characterized by us as counter-art, a becoming-quilombist articulated by black-indigenous artist-activists. This becoming-quilombista is self-defense and counterattack, through artistic guerrilla actions, of the Brazilian Black People.
Keywords: minority tour; becoming-quilombista; art and counter-art; contemporary art